New Determinations of the Atomic Masses of Zn66, Zn67, Zn68 and Ni58 - Isenor, Neil (My University, 1955)
Masses have been determined by means of new mass spectrographic comparisons for the nuclides Zn66, Zn67, Zn68 and Ni58. The values obtained are compared with earlier ones from another laboratory. Mass differences have been obtained, which, together with those from nuclear reaction experiments, provide a basis for the adjustment of former mass values. These adjustments have lead to better agreement between mass determinations and nuclear disintegration data.
Keywords: Zn66; Zn67; Zn68; Ni58; zinc-66; zinc-67; zinc-68; nickel-58; atomic mass; atomic masses